1993
DOI: 10.1007/bf01309784
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of subgroup F adenoviruses to interferon

Abstract: The subgroup F adenoviruses were tested for their ability to induce interferon in semi-permissive human cells (Chang conjunctiva) and non-permissive cells (HEF, human embryo lung fibroblasts). These cells did not produce interferon spontaneously or in response to infection by either of these adenoviruses. It was concluded that interferon induction in response to subgroup F adenovirus infection is not a likely explanation of limited virus growth in culture. Adenovirus 40 and Ad41, unlike Ad2, were found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
2
7
1
Order By: Relevance
“…In our experiments, HAdV-41p appears to be no more sensitive than HAdV-5p to inhibition by IFN (Fig. 6); however, others have noted that HAdV-41 infection is blocked by IFN under conditions permissive for HAdV-2 replication (45). Caveats of these studies include a poorly characterized mixture of IFN-␣ and IFN-␤ derived from Namalwa cells (a B lymphoblast cell line) infected with Sendai virus and infection of cells thought to be conjunctival cells but later shown to be HeLa (45).…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…In our experiments, HAdV-41p appears to be no more sensitive than HAdV-5p to inhibition by IFN (Fig. 6); however, others have noted that HAdV-41 infection is blocked by IFN under conditions permissive for HAdV-2 replication (45). Caveats of these studies include a poorly characterized mixture of IFN-␣ and IFN-␤ derived from Namalwa cells (a B lymphoblast cell line) infected with Sendai virus and infection of cells thought to be conjunctival cells but later shown to be HeLa (45).…”
Section: Discussioncontrasting
confidence: 46%
“…6); however, others have noted that HAdV-41 infection is blocked by IFN under conditions permissive for HAdV-2 replication (45). Caveats of these studies include a poorly characterized mixture of IFN-␣ and IFN-␤ derived from Namalwa cells (a B lymphoblast cell line) infected with Sendai virus and infection of cells thought to be conjunctival cells but later shown to be HeLa (45). Nonetheless, in one study, prior infection with HAdV-2 rescued HAdV-41 from IFN, suggesting that HAdV-2 potently inhibited the antiviral state (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our newly constructed cell line, 293-CMV, may be useful for culturing and analyzing fastidious HAdVs. The fastidious characteristics of HAdVs are thought to be due to the antiviral effect of IFN, the inability of the E1A gene product to transactivate other essential genes, and a block in the release of progeny viruses (4,32,36). A recent study by Sherwood et al demonstrated that the replication of HAdVs can be promoted by reducing the IFN response by the expression of simian virus 5 (SV5) T antigen (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although HAdVs are cultivable in several cell lines, including 293, A549, PLC/PRF5, and Caco-2 cells, they are fastidious and do not produce a clear and consistent cytopathic effect (CPE) within a reasonable time (6, 17-19, 20, 31). They are sensitive to type I interferon (IFN), and the HAdV E1A gene is deficient in its ability to transactivate its own genes (4,23,36,39). These characteristics make cultural analyses of HAdVs difficult because of their low concentrations and the presence of other fast-culturing viral agents in environmental samples.…”
mentioning
confidence: 99%